2018
DOI: 10.1021/acsnano.8b05739
|View full text |Cite
|
Sign up to set email alerts
|

Highly Electrically Conductive Three-Dimensional Ti3C2Tx MXene/Reduced Graphene Oxide Hybrid Aerogels with Excellent Electromagnetic Interference Shielding Performances

Abstract: Two-dimensional transition-metal carbides/carbonitrides (MXenes) with both superb electrical conductivity and hydrophilicity are promising for fabricating multifunctional nanomaterials and nanocomposites. However, the construction of three-dimensional (3D) and lightweight MXene macroscopic assemblies with excellent electrical conductivity and mechanical performances has not been realized due to the weak gelation capability of MXene sheets. Herein, we demonstrate an efficient approach for constructing highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
368
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 740 publications
(394 citation statements)
references
References 71 publications
(129 reference statements)
3
368
0
1
Order By: Relevance
“…Then anocomposite with 0.40 vol% of Ti 3 C 2 T x exhibits as uperb average EMI shielding performance of 34.5 dB over the whole X-band, which is sufficient for many civil and military applications.T he results of SE divided by sample thickness (SE/d)a re summarized in Figure S11 and Table S1 to eliminate the effect of specimen thickness.I ti sw orth noting that the as-prepared Ti 3 C 2 T x @epoxy nanocomposite shows ac ompetitive shielding performance of 17.3 dB mm À1 in comparison to other shielding materials. [32] In summary,wehave demonstrated the interfacial activity of MXSs formed by the interactions between Ti 3 C 2 T x and POSS-NH 2 at the oil-water interface.MXSs rapidly form and assemble at the interface with acontrollable packing density, and when jammed, produce as olid-like assembly with excellent mechanical properties.T aking advantage of MXSs, 2D films,a nd structured Pickering emulsions can be easily prepared. Furthermore,b yfreeze-drying the concentrated emulsion droplets,l ightweight, hydrophobic 3D MXene aerogels are produced from the bottom up,w hich can be used for oil adsorption and EMI shielding.T his intriguing assembly strategy at the liquid-liquid interface provides as imple route to construct MXene assemblies from the mesoscale to macroscale,h aving significant practical importance.…”
Section: Angewandte Chemiementioning
confidence: 65%
See 2 more Smart Citations
“…Then anocomposite with 0.40 vol% of Ti 3 C 2 T x exhibits as uperb average EMI shielding performance of 34.5 dB over the whole X-band, which is sufficient for many civil and military applications.T he results of SE divided by sample thickness (SE/d)a re summarized in Figure S11 and Table S1 to eliminate the effect of specimen thickness.I ti sw orth noting that the as-prepared Ti 3 C 2 T x @epoxy nanocomposite shows ac ompetitive shielding performance of 17.3 dB mm À1 in comparison to other shielding materials. [32] In summary,wehave demonstrated the interfacial activity of MXSs formed by the interactions between Ti 3 C 2 T x and POSS-NH 2 at the oil-water interface.MXSs rapidly form and assemble at the interface with acontrollable packing density, and when jammed, produce as olid-like assembly with excellent mechanical properties.T aking advantage of MXSs, 2D films,a nd structured Pickering emulsions can be easily prepared. Furthermore,b yfreeze-drying the concentrated emulsion droplets,l ightweight, hydrophobic 3D MXene aerogels are produced from the bottom up,w hich can be used for oil adsorption and EMI shielding.T his intriguing assembly strategy at the liquid-liquid interface provides as imple route to construct MXene assemblies from the mesoscale to macroscale,h aving significant practical importance.…”
Section: Angewandte Chemiementioning
confidence: 65%
“…As agraphene-like 2D material, the distinctive properties of MXenes,e specially the high hydrophilicity and metallic conductivity,m ake them attractive for many applications,s uch as energy storage,s ensors,c atalysis,n anocomposites,a nd electromagnetic interference (EMI) shielding. [18,19] Up to now,a pplications of MXenes as building blocks,functional assemblies including one-dimensional (1D) fibers, [20][21][22] 2D films, [23][24][25][26][27] and 3D monoliths [28][29][30][31][32] have been reported through av ariety of assembly strategies.H owever,[*] Prof.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some works report the formation of hybrid graphene/MXene composites [59][60][61][62][63]. GO can help to stabilize the MXene flakes in the suspension forming a composite sol or gel, making it possible to freeze-dry it.…”
Section: Assembly By Induced Gelationmentioning
confidence: 99%
“…One of the first studies of unidirectional freeze-casting of MXenes was reported by Zhao et al to produce a GO-assisted assembled MXene aerogel [61]. Based on the porous architecture, they propose an assembly mechanism as follows: due to their affinity, a stable aqueous Ti 3 C 2 T x /GO suspension is formed.…”
Section: Freeze-castingmentioning
confidence: 99%